2014
DOI: 10.1371/journal.pone.0099922
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Like Domain-Containing Protein 7 (EGFL7) Enhances EGF Receptor−AKT Signaling, Epithelial−Mesenchymal Transition, and Metastasis of Gastric Cancer Cells

Abstract: Epidermal growth factor-like domain-containing protein 7 (EGFL7) is upregulated in human epithelial tumors and so is a potential biomarker for malignancy. Indeed, previous studies have shown that high EGFL7 expression promotes infiltration and metastasis of gastric carcinoma. The epithelial–mesenchymal transition (EMT) initiates the metastatic cascade and endows cancer cells with invasive and migratory capacity; however, it is not known if EGFL7 promotes metastasis by triggering EMT. We found that EGFL7 was ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 59 publications
5
50
0
Order By: Relevance
“…As high EGFL7 expression is associated with acquired chemoresistance, tumor cells that exhibit lower EGFL7 expression may have a greater sensitivity to NAC treatment. In addition, a correlation between EGFL7 and Snail expression levels was observed These results were concordant with a previous study that reported that EGFL7 is able to positively regulate EMT by EGFR-mediated AKT phosphorylation through the activation of Snail expression (27). The results of the current study support the hypotheses that the overexpression of EGFL7 may have a role in the development of tumor chemoresistance through EMT, and increasing resistance to cell apoptosis by activating Snail expression; therefore, EGFL7 may be an effective prognostic factor regarding the efficacy of NAC treatment for locally advanced uterine cervical cancer.…”
Section: No Of Patients --------------------------------------------supporting
confidence: 92%
See 2 more Smart Citations
“…As high EGFL7 expression is associated with acquired chemoresistance, tumor cells that exhibit lower EGFL7 expression may have a greater sensitivity to NAC treatment. In addition, a correlation between EGFL7 and Snail expression levels was observed These results were concordant with a previous study that reported that EGFL7 is able to positively regulate EMT by EGFR-mediated AKT phosphorylation through the activation of Snail expression (27). The results of the current study support the hypotheses that the overexpression of EGFL7 may have a role in the development of tumor chemoresistance through EMT, and increasing resistance to cell apoptosis by activating Snail expression; therefore, EGFL7 may be an effective prognostic factor regarding the efficacy of NAC treatment for locally advanced uterine cervical cancer.…”
Section: No Of Patients --------------------------------------------supporting
confidence: 92%
“…The first hypothesis was that high expression levels of EGFL7 may have a role in the development of chemoresistance due to decreased drug delivery caused by reduced vascular integrity in tumors tissues. The second hypothesis was that the promotion of EMT by EGFL7 may induce the development of tumor cell resistance to chemotherapy; EMT is regulated by EGFR-mediated AKT phosphorylation induced by EGFL7, which then activates Snail and the subsequent suppression of E-cadherin transcription (27). Numerous studies have previously reported that EMT may have a function in acquired chemoresistance (28)(29)(30)(31)(32).…”
Section: No Of Patients --------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that EGF promotes cancer cell migration with activation of EMT (Luo et al, 2014). And EGFL7 contains two EGF-like domains in its protein organization.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the targeting of EMTrelated pathways in human tumor cell lines and murine models revealed the crucial importance of EMT in the aggressiveness and invasion of pancreatic cancer (Kurahara et al, 2012). Luo et al reported that EGFL7 promotes tumor invasion by activating EMT through an EGFR-AKT-Snail signaling pathway in gastric cancer (Luo et al, 2014). Thus, we assumed that EGFL7 may also promote cancer invasion by inducing EMT in pancreatic cancer.…”
mentioning
confidence: 85%